Carbon material dispersion liquid and application thereof

By combining single-layer carbon nanotubes, multi-layer carbon nanotubes and carbon black in the carbon material dispersion, and optimizing the composition ratio and selection of binder resins, the problem of insufficient conductivity of carbon material dispersion in the prior art is solved, and a coating film with improved conductivity is achieved, meeting high-performance needs and providing a variety of application potentials.

CN119604585APending Publication Date: 2025-03-11DAINICHISEIKA COLOR & CHEMICALS MFG CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056410.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-03-22
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing carbon material dispersions fail to show high level of conductivity after forming the coating film, and cannot meet the high performance needs in recent years.

Method used

A carbon material dispersion containing a single layer of carbon nanotube, a multilayer carbon nanotube and carbon black is used, and the carbon material is effectively dispersed and bonded through specific composition ratios and selection of binder resins to ensure effective dispersion and bonding of carbon materials, forming a coating film with improved conductivity.

Benefits of technology

A coating with improved conductivity compared to a single carbon material is achieved, meeting high performance needs and providing application potential for the manufacture of various products and coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257397070000251
    Figure BDA0005257397070000251
  • Figure BDA0005257397070000261
    Figure BDA0005257397070000261
  • Figure BDA0005257397070000271
    Figure BDA0005257397070000271
Patent Text Reader

Abstract

Provided is a carbon material dispersion which is capable of forming a coating film having improved conductivity compared to a case where a single carbon material is used. A carbon material dispersion containing: at least two kinds of carbon materials selected from the group consisting of single-layer carbon nanotubes, multi-layer carbon nanotubes, and carbon black; an aqueous medium; a dispersant; and a binder resin, when the carbon material is a combination of single-layer carbon nanotubes and carbon black, the amount of carbon black is 0.001-0.43 parts by mass per 1 part by mass of single-layer carbon nanotubes, and when the carbon material is a combination of single-layer carbon nanotubes, multi-layer carbon nanotubes, and carbon black, the amount of carbon black is 0.001-0.43 parts by mass per 1 part by mass of the total of single-layer nanotubes and multi-layer carbon nanotubes, and the amount of carbon black is 0.001-0.43 parts by mass per 1 part by mass of the total of single-layer nanotubes and multi-layer carbon nanotubes. And the amount of the carbon black is 0.001 to 0.43 parts by mass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon material dispersion liquid and application thereof. Background Art

[0002] Carbon materials (nanocarbon materials) such as carbon black, carbon fiber, carbon nanotube (hereinafter, also referred to as "CNT"), graphite, and graphene have a six-membered ring graphite structure formed by covalent bonds of carbon atoms. Therefore, in order to exert various properties such as electrical conductivity and thermal conductivity, methods for utilizing their properties in a wide range of fields are being studied. For example, attention is paid to the electrical properties, thermal properties, and properties of carbon materials as fillers, and electrodes for antistatic agents, conductive materials, plastic reinforcement materials, semiconductors, fuel cells, secondary batteries, etc., and cathode lines of displays, etc. are being studied.

[0003] In these applications, high performance has been required in recent years, and CNT has been widely used as a carbon material. It should be noted that in order to improve various physical properties such as conductivity, in addition to the type and amount of the dispersant used to disperse the CNT in the liquid medium, the selection of the binder resin used when forming a coating film, an electrode, etc. is also important.

[0004] As related prior art, for example, a method for evaluating the conductivity of CNTs by measuring the surface resistance of a resin composition containing CNTs and resins synthesized using a specific catalyst, and a coating film containing synthesized CNTs (Patent Document 1) is proposed. In addition, a CNT dispersion liquid containing a single-layer CNT, a multilayer CNT, a dispersant and a solvent, and a non-aqueous electrolyte secondary battery obtained using the CNT dispersion liquid are proposed (Patent Document 2).

[0005] Furthermore, a CNT dispersion and an electrode film for a secondary battery obtained using the CNT dispersion are proposed, wherein the CNT dispersion contains CNTs having an acidic group, a dispersant and water, and the dispersant is a copolymer containing a structural unit derived from (meth) acrylonitrile and a carboxyl group-containing monomer unit (Patent Document 3). In addition, a CNT aqueous dispersion and a conductive film for a solar cell obtained using the CNT aqueous dispersion are proposed, wherein the CNT aqueous dispersion contains a single-layer CNT, acetylene black, a dispersant and water, and the mass ratio of acetylene black / single-layer CNT is 1.4 or less (Patent Document 4).

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2015-123410

[0009] Patent Document 2: Japanese Patent Application Publication No. 2022-079409

[0010] Patent Document 3: Japanese Patent Application Publication No. 2021-190331

[0011] Patent Document 4: International Publication No. 2022 / 064939 Summary of the invention

[0012] Problem that the invention aims to solve

[0013] The carbon material dispersion containing carbon materials such as CNTs is used, for example, as a material for improving the conductivity of a target article, etc. The conductivity of the carbon material dispersion can be evaluated, for example, by measuring the surface resistivity of a coating film formed by applying and drying the carbon material dispersion.

[0014] The present inventors formed a coating film using the existing CNT dispersion liquids proposed in Patent Documents 2 to 4, etc., and measured the surface resistivity of the formed coating film and evaluated the conductivity. The results showed that the coating film formed using any CNT dispersion liquid did not show the high level of conductivity required in recent years.

[0015] The present invention is made in view of the problems of the prior art, and its subject is to provide a carbon material dispersion liquid that can form a coating film with improved conductivity compared with the case of using a single carbon material. In addition, the subject of the present invention is to provide the use of the carbon material dispersion liquid for manufacturing various products and the coating film that becomes the component part of various products.

[0016] Solutions for solving problems

[0017] That is, according to the present invention, the following carbon material dispersion is provided.

[0018] [1] A carbon material dispersion comprising: at least two carbon materials selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black; an aqueous medium; a dispersant; and a binder resin, wherein the carbon material dispersion satisfies the following necessary conditions (1) and (2).

[0019] (1) When the carbon material is a combination of the single-walled carbon nanotube and the carbon black, the amount of the carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the single-walled carbon nanotube,

[0020] When the carbon material is a combination of the multiwalled carbon nanotubes and the carbon black, the amount of the carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the multiwalled carbon nanotubes.

[0021] When the carbon material is a combination of the single-walled carbon nanotubes and the multi-walled carbon nanotubes, the amount of the multi-walled carbon nanotubes is 10 to 100 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes.

[0022] When the aforementioned carbon material is a combination of the aforementioned single-walled carbon nanotubes, the aforementioned multi-walled carbon nanotubes and the aforementioned carbon black, the amount of the aforementioned carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the total of the aforementioned single-walled carbon nanotubes and the aforementioned multi-walled carbon nanotubes, and the amount of the aforementioned multi-walled carbon nanotubes is 10 to 100 parts by mass relative to 1 part by mass of the aforementioned single-walled carbon nanotubes.

[0023] (2) The surface resistivity of a dry film having a carbon material content of 3% by mass and a thickness of 1 μm is 1.0×10 6 Ω / sq or less.

[0024] [2] The carbon material dispersion according to [1], wherein the dispersant is at least any one of a polymer dispersant and a cellulose derivative, and the polymer dispersant is a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid.

[0025] [3] A carbon material dispersion according to the above [2], wherein the above polymer dispersant is a polymer having a carboxyl group at least partly neutralized by an alkali, and having 50 to 80% by mass of the above structural unit (1) and 20 to 50% by mass of the above structural unit (2) (wherein the total of the above structural unit (1) and the above structural unit (2) is set to 100% by mass).

[0026] [4] The carbon material dispersion according to [3], wherein the polymer is an AB block copolymer comprising a polymer segment A and a polymer segment B, wherein the polymer segment A comprises 60 to 95% by mass of a structural unit (1-A) derived from acrylonitrile and 5 to 40% by mass of a structural unit (2-A) derived from methacrylic acid (wherein the total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass), and the polymer segment B comprises 10 to 70% by mass of a structural unit (1-B) derived from acrylonitrile and 30 to 90% by mass of a structural unit (2-B) derived from methacrylic acid (wherein the total of the structural unit (1-B) and the structural unit (2-B) is 100% by mass), the polymer segment A has a number average molecular weight of 10,000 to 100,000 and a molecular weight distribution of 1.8 or less, and the polymer segment B has a number average molecular weight of 3,000 to 200,000.

[0027] [5] The carbon material dispersion according to any one of [1] to [4] above, wherein the binder resin is at least one selected from the group consisting of cellulose derivatives, styrene-butadiene copolymers, and acrylic resins.

[0028] [6] The carbon material dispersion according to any one of the preceding [1] to [5], wherein when the carbon material contains the single-walled carbon nanotubes, the amount of the dispersant is 30 to 200 parts by mass with respect to 100 parts by mass of the single-walled carbon nanotubes; when the carbon material contains the multi-walled carbon nanotubes, the amount of the dispersant is 30 to 200 parts by mass with respect to 100 parts by mass of the multi-walled carbon nanotubes; and when the carbon material contains the carbon black, the amount of the dispersant is 10 to 200 parts by mass with respect to 100 parts by mass of the carbon black.

[0029] [7] The carbon material dispersion according to any one of the preceding [1] to [6], wherein the surface resistivity a (Ω / sq) and the surface resistivity b (Ω / sq) satisfy the relationship a < b, and the surface resistivity a is 5.0×10 5 Ω / sq or less. The surface resistivity a (Ω / sq) is the surface resistivity of the first coating film with a thickness of 1 μm and a carbon material content of 3% by mass formed by coating and drying the carbon material dispersion. The surface resistivity b (Ω / sq) is the surface resistivity of the second coating film with a thickness of 1 μm and a carbon material content of 3% by mass formed by coating and drying the control dispersion. The control dispersion has the same composition as the carbon material dispersion except that it does not contain one of the carbon materials.

[0030] [8] The carbon material dispersion according to any one of the preceding [1] to [7], wherein the average length of the single-walled carbon nanotubes is 5 to 600 μm, and the average length of the multi-walled carbon nanotubes is 40 to 3,000 μm.

[0031] [9] The carbon material dispersion according to any one of the preceding [1] to [8], which is obtained by mixing a first dispersion liquid and a second dispersion liquid. The first dispersion liquid contains at least one of the carbon materials, and the second dispersion liquid contains at least one of the carbon materials different from the carbon materials in the first dispersion liquid.

[0032]

[10] The carbon material dispersion according to any one of the preceding [1] to [9], wherein the absorbance A at a wavelength of 380 nm of the diluted dispersion liquid obtained by diluting with a blank liquid so that the absorbance at a wavelength of 580 nm becomes 1.8 ± 0.02 L relative to the absorbance A at a wavelength of 780 nm H ratio (A L / A H ) is 1.40 or more. The blank liquid has the same composition as the carbon material dispersion except that it does not contain the carbon material and the binder resin.

[0033] Furthermore, according to the present invention, there are provided uses of the carbon material dispersion liquid shown below.

[0034]

[11] Use of the carbon material described in any one of [1] to

[10] above in the manufacture of any product selected from the group consisting of paint, ink, coating agent, resin molding material, conductive material, thermal conductive material, and antistatic material.

[0035]

[12] Use of the carbon material dispersion according to any one of [1] to

[10] above for producing a product including a battery material and a mechanical part having a coating formed of the carbon material dispersion.

[0036] Effects of the Invention

[0037] According to the present invention, a carbon material dispersion liquid can be provided that can form a coating film having improved conductivity compared to the case of using a single carbon material. In addition, according to the present invention, the use of the carbon material dispersion liquid in the manufacture of various products and coating films that become components of various products can be provided. DETAILED DESCRIPTION

[0038] <Carbon Material Dispersion Liquid>

[0039] The following describes an embodiment of the present invention, but the present invention is not limited to the following embodiment. One embodiment of the carbon material dispersion of the present invention contains: at least two carbon materials selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black; an aqueous medium; a dispersant; and a binder resin. Moreover, the carbon material dispersion of this embodiment satisfies the following necessary conditions (1) and (2). The following describes the details of the carbon material dispersion of the present invention (hereinafter also referred to as "dispersion").

[0040] (1) When the carbon material is a combination of single-walled carbon nanotubes and carbon black, the amount of carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes,

[0041] When the carbon material is a combination of multiwalled carbon nanotubes and carbon black, the amount of carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the multiwalled carbon nanotubes.

[0042] When the carbon material is a combination of single-walled carbon nanotubes and multi-walled carbon nanotubes, the amount of the multi-walled carbon nanotubes is 10 to 100 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes.

[0043] When the carbon material is a combination of single-walled carbon nanotubes, multi-walled carbon nanotubes, and carbon black, the amount of carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes and multi-walled carbon nanotubes in total, and the amount of multi-walled carbon nanotubes is 10 to 100 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes.

[0044] (2) The surface resistivity of a dry film having a carbon material content of 3% by mass and a thickness of 1 μm is 1.0×10 6 Ω / sq or less.

[0045] (Carbon material)

[0046] The carbon material is at least two selected from the group consisting of single-layer carbon nanotubes, multi-layer carbon nanotubes and carbon black. The average length of the single-layer carbon nanotubes (hereinafter, also referred to as "SWCNT") is preferably 5 to 600 μm, more preferably 10 to 500 μm. In addition, the average length of the multi-layer carbon nanotubes (hereinafter, also referred to as "MWCNT") is preferably 40 to 3,000 μm. When the dispersion of the present embodiment is used as a constituent material of a battery, in order to make the surface resistivity of the formed coating film lower, the average length of the MWCNT is preferably 100 to 3,000 μm.

[0047] Examples of carbon black (hereinafter also referred to as "CB") include acetylene black, furnace black, thermal black, Ketjen black, etc. The average primary particle size of CB is preferably 10 to 60 nm. The carbon material may be doped with a metal or a metal salt such as platinum or palladium. In addition, the carbon material may be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, etc.

[0048] As a conductive carbon material constituting an electrode, SWCNT is suitable from the viewpoint of cycle characteristics. However, SWCNT is easy to aggregate when a coating is formed, so compared with the case of using MWCNT, there is a tendency that the resistance of the formed coating is equal or above. On the other hand, MWCNT is not easy to aggregate due to easy dispersion, and may reduce the resistance of the formed coating, but in terms of cycle characteristics, there is a tendency to be worse than the case of using SWCNT. Therefore, by using SWCNT and MWCNT in combination at a specified ratio, a dispersion liquid that can form a coating for an electrode with excellent conductivity and cycle characteristics can be made.

[0049] When at least any one of SWCNT and MWCNT is used in combination with CB at a predetermined ratio, the CB is arranged in the formed coating film so as to fill the gaps in the network formed by the fiber-shaped CNT. As a result, the conductive paths increase, so that compared with the case of using CNT alone, even if the content of the carbon material is the same, a coating film with a further reduced surface resistivity can be formed.

[0050] It should be noted that even if CB is not used, the surface resistivity of the formed coating can be reduced by containing a large amount of CNT. However, if the content of CNT in the coating is increased, the content of the binder resin suitable for forming the coating is relatively reduced, so it is difficult to reflect the properties of the binder resin such as elongation and bending. In contrast, in the dispersion of the present embodiment, by combining at least any one of SWCNT and MWCNT with CB at a prescribed ratio, even if CNT is not used excessively, a coating that easily reflects the properties of the binder resin such as elongation and bending can be formed.

[0051] The dispersion liquid of the present embodiment satisfies the following requirement (1). By satisfying the following requirement (1), that is, containing at least two carbon materials at a specific ratio, a coating film having improved conductivity can be formed compared to a case where a single carbon material is contained. (1)

[0053] (1-1) When the carbon material is a combination of SWCNT and CB, the amount of the CB is 0.001 to 0.43 parts by mass, preferably 0.01 to 0.3 parts by mass, based on 1 part by mass of SWCNT.

[0054] (1-2) When the carbon material is a combination of MWCNT and CB, the amount of CB is 0.001 to 0.43 parts by mass, preferably 0.01 to 0.3 parts by mass, based on 1 part by mass of MWCNT.

[0055] (1-3) When the carbon material is a combination of SWCNT and MWCNT, the amount of MWCNT is 10 to 100 parts by mass, preferably 20 to 80 parts by mass, based on 1 part by mass of SWCNT.

[0056] (1-4) When the carbon material is a combination of SWCNT, MWCNT, and CB, the amount of CB is 0.001 to 0.43 parts by mass, preferably 0.01 to 0.3 parts by mass, relative to 1 part by mass of SWCNT and MWCNT in total, and the amount of MWCNT is 10 to 100 parts by mass, preferably 20 to 80 parts by mass, relative to 1 part by mass of SWCNT.

[0057] Furthermore, the carbon material dispersion of the present embodiment satisfies the following requirement (2). That is, by satisfying the above requirement (1), a coating film having improved conductivity that satisfies the following requirement (2) can be formed.

[0058] (2) The surface resistivity of a dry film having a carbon material content of 3% by mass and a thickness of 1 μm is 1.0×10 6 Ω / sq or less, preferably 5.0×10 55.0 × 10 Ω / sq or less.

[0059] By using the carbon material dispersion of the present embodiment, as described above, compared with the case of using a dispersion containing a single carbon material, a coating film with improved conductivity can be formed. Specifically, the surface resistivity a (Ω / sq) of the first coating film with a thickness of 1 μm and a carbon material content of 3% by mass formed by coating and drying the carbon material dispersion (dispersion a) preferably satisfies the relationship of a < b with the surface resistivity b (Ω / sq) of the second coating film with a thickness of 1 μm and a carbon material content of 3% by mass formed by coating and drying the control dispersion (dispersion b), where the control dispersion (dispersion b) has the same composition as the carbon material dispersion (dispersion a) except that it does not contain one of the carbon materials. Moreover, the above-mentioned surface resistivity a is preferably 5.0 × 10 5 5.0 × 10 Ω / sq or less.

[0060] The dispersion of the present embodiment may further contain other carbon materials in addition to the above-mentioned carbon materials. As the other carbon materials, carbon fibers, graphite, graphene, etc. can be used.

[0061] As the carbon fiber, PAN-based carbon fibers made from polyacrylonitrile, pitch-based carbon fibers made from pitch, and their recycled products, etc. can be cited. Among them, carbon nanofibers with a fiber diameter in the nanometer size and a shape of a cylindrical shape with a wound hexagonal ring graphite structure are preferred. Graphite is a layered substance containing a crystal structure composed of carbon. Among them, graphene with a single layer thickness of one atom peeled off from graphite and graphene formed by multiple layers can be used.

[0062] The other carbon materials may be doped with metals, metal salts such as platinum and palladium. In addition, the other carbon materials can be surface-modified by oxidation treatment, plasma treatment, radiation treatment, corona treatment, coupling treatment, etc.

[0063] (aqueous medium)

[0064] The carbon material dispersion of the present embodiment contains an aqueous medium as a liquid medium for dispersing the carbon material. That is, the dispersion of the present embodiment is an aqueous dispersion of the carbon material.

[0065] As the aqueous medium, water or a mixed solvent of water and a water-soluble organic solvent can be used. Examples of the water-soluble organic solvent include alcohols such as methanol, ethanol, and isopropanol; polyols such as ethylene glycol, propylene glycol, and glycerol; ethers such as tetrahydrofuran; glycol ethers such as diethylene glycol, triethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monobutyl ether, ethylene glycol dimethyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol monopropyl ether, dipropylene glycol monomethyl ether, and tripropylene glycol monomethyl ether; glycol ether esters such as diethylene glycol monomethyl ether acetate; amides such as pyrrolidone, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, 3-methoxy-N,N-dimethylpropaneamide, and 3-butoxy-N,N-dimethylpropaneamide; urea-based solvents such as tetramethylurea and dimethyl-1,3-imidazolidinone; sulfur-containing solvents such as dimethyl sulfoxide and cyclopentane; ionic liquids such as 1-ethyl-3-methylimidazolium chloride; and the like. Among them, alcohols and N-methylpyrrolidone (NMP) are preferred.

[0066] The content of the water-soluble organic solvent in the carbon material dispersion is preferably 20% by mass or less, more preferably 10% by mass or less.

[0067] (Dispersant)

[0068] The dispersant is a component for dispersing the carbon material in a liquid medium. As the dispersant, anionic, cationic, nonionic, and amphoteric surfactants; polymer dispersants can be used. Among them, it is preferred to use at least any one of a polymer dispersant and a cellulose derivative as the dispersant.

[0069] Examples of cellulose derivatives include methyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, hydroxypropyl methyl cellulose, and metal salts thereof. Among them, carboxymethyl cellulose and carboxymethyl cellulose sodium salt are preferred. Furthermore, the cellulose derivative preferably has a viscosity of 20 to 500 mPa·s in a 1 mass % aqueous solution and an etherification degree of 0.5 to 0.9. By using such a cellulose derivative, the carbon material can be dispersed more well and the storage stability can be improved.

[0070] The polymer dispersant is preferably a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid, and is preferably a polymer consisting essentially of a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid. In addition, the polymer dispersant is preferably a polymer having carboxyl groups at least partly neutralized by a base.

[0071] Structural unit (1) has a cyano group (-CN) derived from (meth) acrylonitrile. Therefore, the triple bond of the cyano group acts on the surface of the carbon material, and the polymer as a dispersant is electronically adsorbed on the carbon material. In addition, structural unit (2) has a carboxyl group derived from (meth) acrylic acid. Therefore, by neutralizing at least a portion of the carboxyl group with a base to ionize it, the polymer as a dispersant can be dissolved in an aqueous medium. By using a polymer containing these structural units (1) and structural units (2) as a dispersant, the carbon material can be microdispersed in an aqueous medium for a long time.

[0072] The proportion of the structural unit (1) derived from (meth) acrylonitrile in the polymer is 50 to 80% by mass, preferably 55 to 75% by mass. In addition, the proportion of the structural unit (2) derived from (meth) acrylic acid in the polymer is 20 to 50% by mass, preferably 25 to 45% by mass. It should be noted that the total of the structural unit (1) and the structural unit (2) is set to 100% by mass. If the proportion of the structural unit (2) in the polymer is less than 20% by mass, the water solubility of the polymer is insufficient. On the other hand, if the proportion of the structural unit (2) in the polymer exceeds 50% by mass, the water solubility of the polymer becomes too high. Therefore, the viscosity of the carbon material dispersion becomes too high, and the amount of hydrophilic carboxyl groups is large, so the water resistance of the formed coating film is sometimes reduced.

[0073] The high molecular weight dispersant (polymer) may also have other structural units in addition to the structural unit (1) and the structural unit (2). Examples of monomers constituting other structural units include conventionally known styrene monomers, (meth)acrylate monomers, and the like. Among them, it is preferred to use monomers that do not contain easily hydrolyzable structures such as ester bonds and amide bonds. Examples of such monomers include styrene, vinylnaphthalene, vinyltoluene, vinylbiphenyl, vinyl alcohol, and the like.

[0074] The polymer used as the polymer dispersant can be any of a random copolymer and a block copolymer. However, in the case of a random copolymer, since the hydrophilic group and the hydrophobic group are randomly present, the effect of the dispersant is sometimes slightly reduced. In addition, in the case of a high hydrophilic binder resin, the binder resin is significantly affected sometimes. Therefore, the polymer used as the polymer dispersant is preferably a block copolymer.

[0075] The polymer used as the high molecular weight dispersant is preferably an AB block copolymer comprising a polymer segment A and a polymer segment B, wherein the polymer segment A has a structural unit (1-A) derived from acrylonitrile and a structural unit (2-A) derived from methacrylic acid, and the polymer segment B has a structural unit (1-B) derived from acrylonitrile and a structural unit (2-B) derived from methacrylic acid. It should be noted that the polymer segment A is preferably a polymer segment substantially composed of only the structural unit (1-A) derived from acrylonitrile and the structural unit (2-A) derived from methacrylic acid. In addition, the polymer segment B is preferably a polymer segment substantially composed of only the structural unit (1-B) derived from acrylonitrile and the structural unit (2-B) derived from methacrylic acid.

[0076] The ratio of the structural unit (1-A) derived from acrylonitrile in the polymer segment A (hereinafter also referred to as "A chain") is preferably 60 to 95% by mass, more preferably 65 to 90% by mass. In addition, the ratio of the structural unit (2-A) derived from methacrylic acid in the A chain is preferably 5 to 40% by mass, more preferably 10 to 35% by mass. The total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass.

[0077] The A chain is a polymer chain segment having a lower carboxyl content and relatively lower water solubility than the polymer chain segment B (hereinafter also referred to as "B chain"). Therefore, the A chain adsorbed on the carbon material is more difficult to detach than the B chain, and thus has the function of further improving the dispersibility of the carbon material. If the proportion of the structural unit (2-A) in the A chain is less than 5% by mass, the water solubility of the A chain is sometimes insufficient. On the other hand, if the proportion of the structural unit (2-A) in the A chain exceeds 40% by mass, the water solubility of the A chain is sometimes too high, and it becomes easy to detach from the carbon material.

[0078] The number average molecular weight of the polymer segment A (A chain) is preferably 10,000 to 100,000, more preferably 20,000 to 90,000. If the number average molecular weight of the A chain is less than 10,000, the adsorption to the carbon material may be insufficient. On the other hand, if the number average molecular weight of the A chain exceeds 100,000, even if the structural unit (2-A) having a carboxyl group is contained, the water solubility may be insufficient.

[0079] The molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) of the polymer segment A (A chain) is preferably 1.8 or less, more preferably 1.6 or less. By making the molecular weight relatively uniform, it can be uniformly adsorbed by the carbon material, and the dispersibility can be further improved. If the molecular weight distribution (PDI value) of the A chain exceeds 1.8, many polymer segments outside the above-mentioned number average molecular weight range are contained, and the effect of improving the dispersibility may be reduced.

[0080] The proportion of the structural unit (1-B) derived from acrylonitrile in the polymer segment B (B chain) is preferably 10 to 70% by mass, more preferably 15 to 65% by mass. In addition, the proportion of the structural unit (2-B) derived from methacrylic acid in the B chain is preferably 30 to 90% by mass, more preferably 35 to 85% by mass. It should be noted that the total of the structural unit (1-B) and the structural unit (2-B) is set to 100% by mass. The number average molecular weight of the B chain is preferably 3,000 to 200,000, more preferably 5,000 to 60,000. If the number average molecular weight of the B chain is less than 3,000, it tends to be difficult to dissolve in water. On the other hand, if the number average molecular weight of the B chain exceeds 200,000, the viscosity tends to increase excessively and become difficult to disperse.

[0081] The B chain is a polymer segment containing more carboxyl groups and having relatively high water solubility compared to the A chain. If the ratio of the structural unit (2-B) in the B chain is less than 30% by mass, the water solubility of the AB block copolymer as a whole is sometimes insufficient. On the other hand, if the ratio of the structural unit (2-B) in the B chain exceeds 90% by mass, the hydrophilicity sometimes becomes too high. Therefore, sometimes the viscosity of the carbon material dispersion becomes too high, and the water resistance of the formed coating film is reduced.

[0082] The AB block copolymer can be produced, for example, by a living radical polymerization method. It should be noted that the AB block copolymer is composed of acrylonitrile and methacrylic acid, so its structure is easy to control and the molecular weight is also easy to adjust.

[0083] As the base for neutralizing at least a part of the carboxyl groups in the polymer dispersant (polymer), for example, ammonia; organic amines such as triethylamine and dimethylaminoethanol; alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, potassium hydroxide; and the like, conventionally known bases can be used. Among them, from the viewpoints of improving water solubility and improving the conductivity of the coating film due to ionic action, the base is preferably at least one selected from the group consisting of lithium hydroxide, sodium hydroxide, and potassium hydroxide.

[0084] All carboxyl groups in the polymer may be neutralized with a base, but as long as the polymer is soluble in water, it is also preferred to neutralize only a portion of the carboxyl groups with a base. The carboxyl groups (-COOH) that are not neutralized with a base can hydrogen bond with the carbon material. Therefore, if a polymer in which only a portion of the carboxyl groups are neutralized with a base is used as a dispersant, the dispersibility stability of the carbon material dispersion can be further improved. The amount of base used to neutralize the carboxyl groups is preferably an amount equivalent to 50 to 120 mol% of the carboxyl groups, and more preferably an amount equivalent to 70 to 110 mol% of the carboxyl groups.

[0085] The polymer used as a polymer dispersant can be manufactured according to the conventionally known method. Among them, it can be manufactured by a solution polymerization method using an organic solvent; a free radical polymerization method using an azo-based free radical initiator or a peroxide-based free radical initiator; etc. As an organic solvent, conventionally known organic solvents can be used. However, polymers are sometimes not easily dissolved in general organic solvents, so it is preferred to use a polar organic solvent that can be dissolved in water. As such a polar organic solvent, amide solvents, sulfoxide solvents, urea solvents, and nitrile solvents can be cited. Among them, amide solvents, urea solvents, and nitrile solvents are preferably used. After polymerization in these organic solvents, an alkaline aqueous solution is added to neutralize the carboxyl group, and the aqueous solution is formed, thereby obtaining a carbon material dispersion containing an organic solvent.

[0086] Examples of amide solvents include dimethylformamide, dimethylacetamide, diethylacetamide, N-methylpyrrolidone, 3-methoxy-N,N-dimethylpropionamide, 3-butoxy-N,N-dimethylpropionamide, etc. Examples of urea solvents include tetramethylurea, 1,3-dimethylimidazolidinone, etc. Examples of nitrile solvents include acetonitrile, etc.

[0087] It is difficult to manufacture the AB block copolymer used as a polymer dispersant by conventional free radical polymerization. Therefore, the AB block copolymer is preferably manufactured by a polymerization method with activity such as living anion polymerization, living cationic polymerization, and living free radical polymerization. Among them, from the viewpoints of conditions, materials, and devices, living free radical polymerization is particularly preferred.

[0088] As living radical polymerization, atom transfer radical polymerization (ATRP), reversible addition fragmentation type chain transfer polymerization (RAFT), nitroxide free radical regulation polymerization (NMP), organic tellurium regulation polymerization (TERP), reversible chain transfer catalytic polymerization (RTCP), reversible complex mediated polymerization (RCMP) etc. can be cited. Among them, preferably use organic compound as catalyst and use organic iodide as polymerization initiation compound RTCP, RCMP method. These methods use safer commercially available compounds, do not use heavy metals, special compounds, cost and purification aspects are advantageous. And then, by making the growth end become trivalent iodine, thus can easily form accurate block structure with general equipment.

[0089] When producing the AB block copolymer, any polymer segment of polymer segment A and polymer segment B may be polymerized first. However, if polymer segment B is polymerized first, methacrylic acid may remain in the polymerization system. In this case, an excessive amount of structural units derived from methacrylic acid may be introduced into the polymer segment A polymerized later. Therefore, it is preferred to polymerize polymer segment A first and then polymerize polymer segment B.

[0090] When the carbon material contains SWCNT, the amount of the dispersant (D / P) is preferably 30 to 200 parts by mass, more preferably 50 to 150 parts by mass, relative to 100 parts by mass of SWCNT. When the carbon material contains MWCNT, the amount of the dispersant (D / P) is preferably 30 to 200 parts by mass, more preferably 30 to 100 parts by mass, relative to 100 parts by mass of MWCNT. In addition, when the carbon material contains CB, the amount of the dispersant (D / P) is preferably 10 to 200 parts by mass, more preferably 20 to 100 parts by mass, relative to 100 parts by mass of CB. By setting the amount of the dispersant relative to the carbon material to the above range, a carbon material dispersion in which the carbon material is more stably dispersed can be prepared. If the amount of the dispersant relative to the carbon material is too small, the dispersant cannot fully cover the surface of the carbon material, and sometimes the dispersibility becomes slightly insufficient. On the other hand, if the amount of the dispersant relative to the carbon material is too much, sometimes the carbon material dispersion tends to thicken, and the ratio of the carbon material in the solid component becomes relatively low. In addition, the surface resistivity of the formed coating film may be slightly high, and when an electrode is formed, the cycle characteristics of the electrode may be deteriorated.

[0091] (Binder resin)

[0092] The carbon material dispersion of this embodiment contains a binder resin. By containing a binder resin, a conductive coating film having excellent properties such as elongation and bending and improved adhesion to a substrate can be formed. As the binder resin, a cellulose derivative such as carboxymethyl cellulose (including Na salt), a styrene-butadiene copolymer, and an acrylic resin such as a styrene-acrylic resin are preferably used in consideration of affinity with a dispersant.

[0093] The content of the binder resin in the carbon material dispersion, when used as a coating or a coating, is preferably set to 0.3 to 200 parts by mass, and more preferably 3 to 100 parts by mass, relative to 1 part by mass of the carbon material. If the amount of the binder resin is too small, it is sometimes difficult to apply to the substrate, and a uniform coating cannot be obtained. If the amount of the binder resin is too much, the ratio of the carbon material is relatively reduced, so sometimes sufficient conductivity cannot be obtained when the coating is made. In the case of battery use, for example, it is preferably set to 0.5 to 500 parts by mass, and more preferably 5 to 300 parts by mass, relative to 1 part by mass of the carbon material. If the amount of the binder resin is too small, it is sometimes difficult to apply to the substrate, and a homogeneous electrode cannot be obtained. If the amount of the binder resin is too much, the ratio of the active material (carbon material) is relatively reduced, so sometimes sufficient battery capacity cannot be obtained when the battery is made.

[0094] (Additives, etc.)

[0095] The carbon material dispersion of the present embodiment may also contain additives, resins, etc. As additives, water-soluble dyes, pigments, ultraviolet absorbers, light stabilizers, antioxidants, leveling agents, defoamers, preservatives, mildew inhibitors, photopolymerization initiators, and other pigment dispersants may be cited. As resins, polyolefin resins, polyhalogenated olefin resins, polyester resins, polyamide resins, polyimide resins, polyether resins, polyvinyl resins, polystyrene resins, polyvinyl alcohol resins, polymethacrylate resins, polyurethane resins, polyepoxy resins, phenolic resins, polyurea resins, polyether sulfone resins, etc. may be cited.

[0096] The carbon material dispersion preferably contains a defoamer as an additive according to the device used in the wetting and dispersing process. If a defoamer is contained, foaming during the dispersion process can be suppressed, so the shear force, impact force, etc. applied during the dispersion process work effectively, and a dispersion with better dispersibility can be made.

[0097] (Carbon material dispersion)

[0098] The absorbance of the dispersion of the carbon material containing carbon nanotubes forms a gentle curve in the wavelength range of 300nm to 1,000nm. However, this curve (absorbance curve) varies greatly depending on the dispersion state of the carbon nanotubes. For example, the absorbance on the short wavelength side shows a large value when the amount of micro-dispersed carbon nanotubes is large. On the other hand, the absorbance on the long wavelength side shows a large value when the amount of aggregates of carbon nanotubes is large. Therefore, the absorbance on the short wavelength side (A L ) divided by the absorbance on the long wavelength side (A H ) and the absorbance ratio (A L / A H) well reflects the dispersion state of the carbon material in the liquid medium. That is, the finer and more uniformly dispersed the carbon nanotubes are, the greater the absorbance ratio is, and if the carbon nanotubes are aggregated, the absorbance ratio is small.

[0099] The wavelength W used as the reference M Let the wavelength W on the short wavelength side L and the wavelength W on the long wavelength side H The central value (W M =(W L +W H ) / 2). Since the wavelength region near the central value is hardly affected by the dispersion state of the carbon material, it is suitable as a criterion for evaluating the dispersibility of the carbon material.

[0100] The wavelength W on the short wavelength side is arbitrarily selected from the range of 350 to 550 nm, preferably from the range of 350 to 450 nm, more preferably from the range of 350 to 400 nm. L The change of absorbance at the wavelength within the above range is clear, and there is little noise and specific peak change, which can be measured stably. If it is lower than 350nm, the absorption and scattering of light by the particles will have an irregular effect, and the peak will change greatly as the dispersion proceeds, making it difficult to use it as an accurate indicator. On the other hand, if it exceeds 550nm, the change of absorbance becomes unclear.

[0101] The wavelength W on the long wavelength side is arbitrarily selected from the range of 650 to 850 nm, preferably from the range of 700 to 850 nm, and more preferably from the range of 700 to 800 nm. H . When the wavelength is within the above range, the proportion of the absorption component is small, and the absorbance of particles with a large proportion of the scattering component can be confirmed. In addition, the noise and specific peak changes are small, and stable measurement can be achieved. If it exceeds 850nm, noise is mixed into the peak, and it is difficult to measure the correct value. On the other hand, when it is lower than 650nm, it is a range that is not suitable as an indicator.

[0102] Wavelength W L With wavelength W H The difference between the wavelength W is preferably 100 nm or more, more preferably 200 nm or more. L With wavelength W H The difference between the wavelength W and the wavelength W is set to be greater than 100 nm, so that the dispersion of the carbon material can be read more accurately. L With wavelength W H If the difference is too small, it may be difficult to accurately evaluate the dispersion state of the carbon material.

[0103] The absorbance of the dispersion varies according to the content (concentration) of the carbon material. Therefore, the absorbance of the dilute dispersion prepared by diluting the dispersion containing the binder resin and the dispersion containing the binder resin is measured. As the diluent for diluting the dispersion, it is preferred to use a blank solution having the same composition as the dispersion as the object except that the carbon material is not contained. By using such a blank solution, the diffusion, reaggregation, and environmental influence on the absorbance of the particles are suppressed, and the absorbance can be more accurately measured by being less susceptible to the influence of the polymer dispersant sometimes used as a dispersant.

[0104] In order to accurately measure the absorbance, it is usually preferred to set the content of the carbon material in the sample solution (dilute dispersion) to a range of 0.001 to 0.01 mass %. If it exceeds 0.01 mass %, the amount of laser scattered light transmitted during the measurement is small, and it is sometimes difficult to accurately measure. On the other hand, if it is less than 0.001 mass %, the value of the absorbance becomes too small, and it is sometimes difficult to accurately evaluate and compare.

[0105] The wavelength W of the dilute dispersion obtained by diluting with a diluent containing a liquid medium is M The absorbance is 1.2 to 2.2, preferably 1.5 to 2.0. M If the absorbance is less than 1.2, it is difficult to determine the dispersion state. On the other hand, it is difficult to accurately measure the absorbance exceeding 2.2.

[0106] Wavelength W of dilute dispersion L The absorbance A L Relative to wavelength W H The absorbance A H The ratio (A L / A H ) value according to the wavelength W H and W L For example, the wavelength W L =380nm and wavelength W H =780nm "A L / A H When the value of " is "1.60", the wavelength W L =400nm and wavelength W H =700nm "A L / A H The value of " is "1.44", the wavelength W L =350nm and wavelength W H =800nm ​​"A L / A H " is 1.78. In addition, the wavelength W L =380nm and wavelength W H =780nm "AL / A H When the value of " is "1.65", the wavelength W L =400nm and wavelength W H =700nm "A L / A H The value of " is "1.48", the wavelength W L =350nm and wavelength W H =800nm ​​"A L / A H The value of " is "1.85".

[0107] Wavelength W L The absorbance of the dilute dispersion at wavelength W is a physical property value that is an indicator of the dispersion state of the carbon material. H The absorbance of the dilute dispersion at wavelength W is a physical property value that is an indicator of the aggregation state of the carbon material. L The absorbance A L Relative to wavelength W H The absorbance A H The ratio (A L / A H ) value, the dispersion state of the carbon material in the dispersion can be accurately evaluated. The dilute dispersion is measured at a wavelength W L and W H The central value is the wavelength W M As a benchmark, take the wavelength W M The sample was diluted with a diluent containing a liquid medium so that the absorbance of the sample became 1.2 to 2.2.

[0108] For dilute dispersions, when the wavelength W L The wavelength is 380nm and W H is 780nm, and the wavelength W M is 580nm, and the wavelength W M When the absorbance under the condition of 1.5 to 2.0 (preferably 1.8 ± 0.02), the absorbance A L Relative to absorbance A H The ratio (A 380 / A 780 ) is preferably 1.40 or more, more preferably 1.48 or more, and particularly preferably 1.55 or more. 380 / A 780 ) is set to the above range, so that even if the types and addition amounts of the carbon material, dispersant, and binder resin are changed, coarse aggregates are substantially not contained, and a dispersion having better viscosity stability can be prepared.

[0109] The absorbance ratio of the dispersion is preferably high regardless of the presence or absence of a binder resin. Even if a binder resin is added to a poorly dispersed dispersion that does not contain a binder resin, the absorbance ratio is hardly improved, and sufficient performance may not be achieved.

[0110] The dispersion of the present embodiment does not easily change in viscosity even after a long period of time, and has excellent viscosity stability (storage stability). Specifically, the change rate of the viscosity (mPa·s) of the dispersion without the binder resin at 25°C after 10 days at room temperature (25°C) is usually 15% or less, preferably 10% or less, and more preferably 5% or less, based on the viscosity (mPa·s) of the dispersion just after preparation (dispersion) and the dispersion after adding the binder resin at 25°C.

[0111] If aggregates with a short side of 100 μm or more are present in the dispersion, when the dispersion is applied to various purposes, the original performance of the carbon nanotubes, such as electrical conductivity and thermal conductivity, is difficult to exert, and the growth and sedimentation of aggregates occur, so that the viscosity stability and storage stability are easily reduced. For example, if a dispersion containing aggregates with a short side of 100 μm or more is used as a coating material, there is a tendency for uniform coating to become difficult. In contrast, the dispersion of the present embodiment does not substantially contain coarse aggregates formed by the carbon material containing carbon nanotubes. Specifically, even if the dispersion just prepared (dispersed), the dispersion after adding the binder resin, and the dispersion after 10 days at room temperature (25°C) are observed 5 times with an optical microscope at a magnification of 200 times, usually no aggregates with a short side of 100 μm or more are observed. Preferably, the number (average value) of aggregates with a short side of 20 μm or more is 10 or more per observation. More preferably, the number (average value) of aggregates with a short side of 20 μm or more is 1 or more and less than 10 per observation, and particularly preferably, no aggregate with a short side of 20 μm or more is observed even after 5 observations.

[0112] (Method for producing carbon material dispersion)

[0113] For the carbon material dispersion, a dispersant is used, and the carbon material containing carbon nanotubes is preliminarily wetted and dispersed in a liquid medium according to a conventionally known method, and then a binder resin is added to produce it. For example, a wetting method, a dispersion method, and a mixing method using a magnetic stirrer, a dissolver, a three-roller kneading, an ultrasonic dispersion, a bead mill dispersion, an emulsifier, a homogenizer, etc. can be used. From the perspective of the simplicity of the process, it is preferably stirred with a magnetic stirrer, a dissolver, and a homogenizer to make it wet, and it is preferably dispersed in combination with a high-pressure homogenizer. For example, it is preferably dispersed by a bead mill using beads of small particle size. In addition, considering the damage to carbon materials such as carbon nanotubes, a wet stirring and high dispersion method can also be combined.

[0114] In addition, it is preferred that each carbon material is dispersed in an aqueous medium to obtain a plurality of dispersions, and then the obtained plurality of dispersions are mixed to manufacture the target carbon material dispersion. That is, the dispersion of the present embodiment is preferably obtained by mixing the first dispersion and the second dispersion, wherein the first dispersion contains at least one of the carbon materials, and the second dispersion contains at least one of the carbon materials that is different from the carbon material in the first dispersion. By mixing a plurality of dispersions obtained by respectively dispersing under appropriate conditions corresponding to the types of carbon materials, a dispersion with better dispersibility can be made. The mechanism of obtaining a dispersion that further improves the dispersibility of the carbon material by mixing a plurality of dispersions (the first dispersion and the second dispersion) may not be clear, and it is substantially difficult or impossible to grasp the mechanism by analysis, etc. It should be noted that in the case of manufacturing a dispersion containing three kinds of carbon materials (SWCNT, MWCNT, and CB), the first dispersion, the second dispersion, and the third dispersion containing the three kinds of carbon materials, respectively, can be mixed.

[0115] When mixing a plurality of dispersions, a disperser may be used in addition to a magnetic stirrer. Mixing using a disperser is preferred because it is possible to prevent impact aggregation and the like, thereby obtaining a dispersion with a better dispersion state.

[0116] (Coating)

[0117] By applying and drying the carbon material dispersion of the present embodiment, a conductive coating (film) can be formed. The concentration of the carbon material in the formed coating is, for example, preferably 1 to 10% by mass, more preferably 2 to 7% by mass, and particularly preferably 3 to 5% by mass. In addition, the thickness of the coating (film thickness) can be, for example, 1 to 10 μm. The thicker the film thickness and the higher the concentration of the carbon material, the lower the surface resistivity of the coating. It was confirmed that when the film thickness is within the range of 1 ± 0.2 μm and the concentration of the carbon material is within the range of 3 ± 0.1% by mass, the surface resistivity of the coating hardly changes.

[0118] The surface resistivity of a dry film (coating film) having a carbon material content of 3% by mass and a thickness of 1 μm formed by applying and drying the carbon material dispersion of the present embodiment is 1.0×10 6 Ω / sq or less, preferably 5.0×10 5 Ω / sq or less. In addition, the surface resistivity of a dry film having a carbon material content of 3% by mass and a thickness of 10 μm formed by applying and drying the carbon material dispersion of this embodiment is preferably 1.0×10 3 Ω / sq or less, more preferably 1.0×10 2The content of the carbon material in the dry film (coating film) can be calculated by subtracting the mass (solid content) of the used dispersant from the mass of the dry film formed by heating the coating film formed by applying the dispersion to evaporate the aqueous liquid medium.

[0119] <Use of Carbon Material Dispersion Liquid>

[0120] In the carbon material dispersion of the present embodiment, the carbon material containing carbon nanotubes does not substantially produce coarse aggregates, but is well dispersed, and has excellent viscosity stability. In addition, the carbon material dispersion of the present embodiment is an aqueous dispersion, so it is an environmentally friendly material, and is useful as a material for manufacturing coatings, inks, coating agents, resin molding materials, etc. In addition, in addition to being expected to be used as a conductive material and a thermal conductive material, it can also be expected to be used in antistatic materials. Furthermore, it is useful as a material for forming a battery material such as an electrode material for a battery such as a lithium ion battery, a fuel cell, a film of a capacitor material, and a film constituting various mechanical parts.

[0121] Aqueous paints and inks can be prepared by adding various components such as solvents, resins, and additives to a carbon material dispersion. Alternatively, the carbon material dispersion may be added to commercially available paints and inks.

[0122] The resin molded product can be manufactured by, for example, removing water after adding a carbon material dispersion to a molten plastic material. In addition, the resin molded product dispersed with carbon material can also be manufactured by removing water or precipitating the carbon material after adding a carbon material dispersion to a fine powder plastic material.

[0123] Example

[0124] Hereinafter, the present invention will be specifically described based on Examples, but the present invention is not limited to these Examples. It should be noted that "parts" and "%" in Examples and Comparative Examples are based on mass unless otherwise specified.

[0125] <Material preparation>

[0126] The carbon material, dispersant, and binder resin shown below were prepared.

[0127] (Carbon material)

[0128] [Single-walled carbon nanotube (SWCNT)]

[0129] SWCNT-1: Trade name "Tuball", manufactured by OCSiAl

[0130] SWCNT-2: Trade name "SG101", manufactured by Zeon Corporation, Japan

[0131] [Multi-walled carbon nanotubes (MWCNT)]

[0132] MWCNT-1: Trade name "100T", manufactured by KUMHO

[0133] MWCNT-2: Trade name "400T", manufactured by KUMHO

[0134] MWCNT-3: Trade name "6A", manufactured by JEIO

[0135] MWCNT-4: Trade name "Multi-walled carbon nanotube sheet", manufactured by Hamamatsu Carbonics Corporation

[0136] [Carbon black (CB)]

[0137] CB-1: Trade name "Li435", manufactured by Denka Co., Ltd.

[0138] CB-2: Trade name "HS-100", manufactured by Denka Co., Ltd.

[0139] CB-3: Trade name "Vulcan XC-72", manufactured by CABOT

[0140] CB-4: Trade name: Ketjen Black EC300J, manufactured by LION SPECIALTY CHEMICALS CO., Ltd.

[0141] (Dispersant)

[0142] Dispersant d: Trade name "FLOWLEN GW-1500", manufactured by Kyoeisha Chemical Co., Ltd., solid content 100%

[0143] Dispersant e: Trade name "DISPARLON AQ-380", manufactured by Kusumoto Chemicals Co., Ltd., solid content 30%

[0144] (Binder resin)

[0145] Adhesive A: Trade name "YL-1098", styrene acrylic resin, manufactured by Starlight PMC

[0146] Binder B: Dispersant c

[0147] Binder C: a mixture of dispersant c and styrene butadiene copolymer latex (trade name: "NALSTER SR-112", manufactured by NIPPON A&L INC.) (dispersant c: styrene butadiene copolymer latex = 4:1)

[0148] <Manufacturing of Dispersant (1)>

[0149] (Dispersant a)

[0150] 233.3 parts of N-methylpyrrolidone (NMP) were placed in a reaction container and stirred, and the temperature was raised to 70°C. In addition, 60 parts of acrylonitrile (AN), 40 parts of acrylic acid (AA), and 3.0 parts of 2,2'-azobis(2,4-dimethylvaleronitrile) (trade name "V-65", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (V-65) were placed in a beaker, and V-65 was completely dissolved to prepare a monomer solution. The prepared monomer solution was placed in a dropping funnel, and 1 / 3 of the total amount was added when the temperature in the reaction container reached 70°C, and the remaining liquid was added dropwise over 1.5 hours. After the addition was completed, 1.0 part of V-65 was added after 2.5 hours. After maintaining at 70°C for 1 hour, the temperature was raised to 80°C and maintained for 2 hours to form a polymer. After cooling, the solid content was measured using a moisture meter, and it was confirmed that almost all the monomers were consumed. The number average molecular weight (Mn) of the polymer calculated as polymethyl methacrylate, measured by gel permeation chromatography (GPC) using a lithium bromide N,N-dimethylformamide solution (lithium bromide concentration: 10 mmol / L) as a developing solvent, was 25,300, and the molecular weight distribution (PDI = weight average molecular weight (Mw) / number average molecular weight (Mn)) was 2.24.

[0151] 24.4 parts of sodium hydroxide (NaOH) (110 mol% relative to AA) and 96.8 parts of ion exchange water were placed in a beaker to completely dissolve NaOH to prepare a NaOH aqueous solution. After the temperature in the reaction container became below 60°C, the NaOH aqueous solution was added to neutralize the carboxyl group to obtain a solution of a polymer dispersant (dispersant a). The solid content of the obtained solution of dispersant a was 22.1%.

[0152] (Dispersant b)

[0153] 255.4 parts of 3-methoxy-N,N-dimethylpropaneamide (MDMPA), 1.0 part of iodine, 3.7 parts of 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile) (trade name "V-70", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) (V-70), 0.2 parts of diphenylmethane (DPM), 106.1 parts of AN, and 26.5 parts of methacrylic acid (MAA) were placed in a reaction container. Stirring was performed while nitrogen was circulated, the temperature was raised to 40°C, and polymerization was performed for 4 hours to form the A chain. The solid content of the reaction solution was 34.8%, and the polymerization conversion calculated from the solid content was about 100%. The Mn of the formed A chain was 14,800, the PDI was 1.41, and the peak molecular weight (PT) was 20,700.

[0154] After adding 3.1 parts of V-70, a monomer solution containing 30.0 parts of AN, 31.8 parts of MAA, and 216.9 parts of MDMPA was further added. Thereafter, polymerization was carried out at 40°C for 4 hours to form a B chain and obtain an AB block copolymer. The solid content of the reaction solution was 29.9%, confirming that the target product was obtained basically quantitatively. The Mn of the obtained AB block copolymer was 21,600, the PDI was 1.52, and the PT was 32,700. The molecular weight of the B chain can be calculated by subtracting the Mn of the A chain from the Mn of the AB block copolymer. That is, the Mn of the B chain is 6,800 and the PT is 12,000.

[0155] 29.8 parts of NaOH (110 mol% relative to MAA) and 105.1 parts of ion exchange water were placed in a beaker to completely dissolve NaOH to prepare a NaOH aqueous solution. The NaOH aqueous solution was added to a reaction vessel to neutralize the carboxyl group to obtain a solution of a polymer dispersant (dispersant b). The solid content of the obtained solution of dispersant b was 25.1%.

[0156] (Dispersant c)

[0157] 400 g of isopropyl alcohol (IPA) and 60 g of water were placed in a 1L stainless steel container equipped with a stirrer, and 10 g of sodium hydroxide (purity 98%) was added while cooling the stainless steel container. After the solution was cooled to below 25°C, 20 g of crushed pulp was added while stirring. Then, stirring and mixing (mercerization) was performed at 15 to 25°C for 60 minutes to prepare alkali cellulose. Then, while cooling the stainless steel container and maintaining it at 15 to 25°C, 30 g of a mixed solution of monochloroacetic acid / isopropyl alcohol = 1:2 was added and stirred and mixed for 15 minutes. Then, while heating the stainless steel container, the temperature of the solution was raised to 70°C in about 30 minutes. Etherification reaction was performed by stirring at 65 to 75°C for 120 minutes. After the reaction was completed, the unreacted sodium hydroxide was neutralized with acetic acid to separate the product. The by-products were removed by washing with a 70% methanol aqueous solution. The product was dried and pulverized to obtain carboxymethyl cellulose sodium salt (dispersant c). The viscosity of a 1% aqueous solution of the obtained carboxymethyl cellulose sodium salt was 31 mPa·s, and the degree of etherification (DS) was 0.84.

[0158] The degree of etherification is measured with reference to the JIS test method for synthetic detergents described in Oil Chemistry 38 (11), 962-967, 1989. Specifically, approximately 1 g of sodium carboxymethyl cellulose is accurately weighed, placed in a magnetic crucible, and heated for 1 hour at a temperature not exceeding 600°C (approximately 550 to 590°C) for incineration. After cooling to room temperature, the crucible is transferred to a 500 mL beaker and 250 mL of water is added. 50 mL of a 0.05 mol / L aqueous sulfuric acid solution is added and boiled for 30 minutes. After cooling to room temperature, the unreacted acid is titrated with 0.1 mol / L sodium hydroxide. Phenolphthalein is used as an indicator. The amount of 0.1 mol / L sodium hydroxide used in the titration is set to "X" mL, and the degree of etherification (DS) is calculated by the following formula.

[0159] Degree of etherification (DS) = 162X / (10000-80X)

[0160] <Measurement and Evaluation Methods>

[0161] (Measurement of absorbance and calculation of absorbance ratio)

[0162] Prepare a blank solution of the same composition as the dispersion except that it does not contain carbonaceous materials. On the basis of measuring the baseline using the prepared blank solution, measure the absorbance of the sample solution. The absorbance of the sample solution is measured using a spectrophotometer (trade name "Hitachi Spectrophotometer U-3310", manufactured by Hitachi High-Technologies Corporation) equipped with a quartz sample cell (cell) with an optical path length of 10 mm. Regarding the dilution based on the blank solution, a standard curve is prepared by plotting the absorbance at a wavelength of 580 nm caused by the change in the dilution ratio, and the dilution ratio at which the aforementioned absorbance becomes 1.8±0.02 is calculated, thereby preparing a dispersion diluted to the target concentration. In addition, it is also possible to adjust the target carbon component concentration at the stage before dispersion, or to adjust the carbon component concentration to meet the aforementioned absorbance at the initial mixing stage and disperse. For the specific method of preparing the sample solution, first collect the dispersion in a polyethylene bottle (polyethylene bottle), and add an appropriate amount of blank solution based on the dilution ratio obtained by the standard curve. The mixture was stirred for 30 seconds using a vortex mixer (manufactured by Scientific Industries, Inc.) to obtain the absorbance A at a wavelength of 580 nm. 580 The absorbance A of the sample solution obtained at a wavelength of 380 nm was measured. 380 and the absorbance A at a wavelength of 780 nm 780 , and calculate the absorbance ratio (A 380 / A 780 ). The measurement was performed on the dispersion immediately after dispersion and the dispersion after addition of the binder resin.

[0163] (Evaluation of dispersion)

[0164] [Measurement of viscosity and evaluation of viscosity stability]

[0165] Using an E-type viscometer with a rotor of 1°34'×R24, the viscosity of the dispersion just after dispersion, the dispersion after adding the binder resin, and each dispersion after 10 days (after standing at room temperature for 10 days) was measured at a temperature of 25°C and a rotor speed of 100 rpm. It should be noted that for dispersions with a viscosity lower than 25 mPa·s, the viscosity was measured using the trade name "VISCOMETER TVE-25L" (manufactured by Toki Sangyo Co., Ltd.). In addition, for dispersions with a viscosity of more than 25 mPa·s, the viscosity was measured using the trade name "VISCOMETER TVE-25H" (manufactured by Toki Sangyo Co., Ltd.). Then, the viscosity stability of the dispersion was evaluated according to the evaluation criteria shown below.

[0166] ◎: The change in viscosity after 10 days from the viscosity immediately after dispersion is less than 5%

[0167] ○: The change rate of viscosity after 10 days based on the viscosity immediately after dispersion is 5% or more and less than 10%

[0168] △: The change rate of viscosity after 10 days based on the viscosity immediately after dispersion is 10% or more and less than 15%

[0169] ×: The change rate of viscosity after 10 days based on the viscosity immediately after dispersion is 15% or more

[0170] [Aggregate observation]

[0171] The dispersion just after dispersion and the dispersion after adding the binder resin were collected in a polyethylene bottle (polyethylene bottle), and a blank solution was added to dilute the dispersion in such a way that the concentration of the carbon material became 0.1% by mass. A vortex mixer (manufactured by Scientific Industries, Inc.) was used to stir for 30 seconds to obtain a dilution. 30 μL of the obtained dilution was added dropwise to a slide glass, and after a cover glass was placed, an optical microscope was used to observe (200 times) the presence or absence of aggregates. For the dispersion just after dispersion, the dispersion after adding the binder resin, and each dispersion after 10 days (after standing at room temperature for 10 days), samples were prepared by dropping 5 times onto the slide glass and observing them, and the presence or absence of aggregates was evaluated according to the evaluation criteria shown below.

[0172] ⊚: No aggregates with a short side of 20 μm or more were observed in the five observations.

[0173] ○: The number (average value) of aggregates with a short side of 20 μm or more was 1 or more and less than 10 in each observation, and no aggregates with a short side of 100 μm or more were observed in 5 observations.

[0174] △: The number (average value) of aggregates with a short side of 20 μm or more was 10 or more per observation, and no aggregates with a short side of 100 μm or more were observed in 5 observations.

[0175] ×: One or more aggregates with a short side of 100 μm or more were observed in five observations.

[0176] (Evaluation of coating film)

[0177] [Measurement of surface resistivity]

[0178] Surface resistivity exceeds 10 5 In the case of Ω / sq, a high resistance resistivity meter (trade name "Hiresta-UPMCP-HT450", manufactured by Mitsubishi Chemical Analytech Co., Ltd.) was used to calculate the average surface resistivity of the coating film obtained by measuring 5 points under an applied voltage of 10 V. In addition, the surface resistivity is 10 5 When it is Ω / sq or less, the average value of the surface resistivity of the coating film measured at 5 points under application of 10 V was calculated using a low-resistance resistivity meter (trade name "Loresta-GP MCP-T610", manufactured by Mitsubishi Chemical Analytech Co., Ltd.).

[0179] <Preparation and evaluation of dispersion (1)>

[0180] (Dispersion 1-25)

[0181] The dispersant and water of the type and amount shown in Table 1 are placed in a polyethylene bottle (polyethylene bottle) with a capacity of 200 mL. After stirring with a magnetic stirrer until uniform, the carbon material of the type and amount shown in Table 1 is added and further stirred. Next, a high-pressure homogenizer (manufactured by Changguang Co., Ltd.) is used to perform high-pressure treatment under the condition of a treatment pressure of about 10 MPa. Thereafter, a high-pressure homogenizer (manufactured by Sugino Machine Limited) is used to perform high-pressure dispersion treatment under the condition of a treatment pressure of about 100 MPa to obtain a dispersion liquid without a binder resin.

[0182] Table 1

[0183]

[0184] (Mixed solution 1~39)

[0185] The first dispersion and the second dispersion before adding the binder resin of the type shown in Table 2 were mixed in such a manner that the carbon material 1 and the carbon material 2 had a mass ratio shown in Table 2, and then mixed using a magnetic stirrer to obtain a mixed solution. The evaluation results of the viscosity stability of a part of the obtained mixed solution, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 3.

[0186] Table 2

[0187]

[0188] Table 3

[0189]

[0190] (Examples 1 to 37, Reference Examples 1 to 8, Comparative Examples 1 to 4)

[0191] The mixed solution and the binder of the types shown in Table 4 were blended at a ratio such that the concentration of the carbon material in the formed coating film (solid content) became the value (%) shown in Table 4, and then mixed using a magnetic stirrer to obtain a carbon material dispersion. The obtained carbon material dispersion was applied to a PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) with a thickness of 100 μm using a rod coater, and then dried in an electric oven at 90°C for 30 minutes to remove volatile components, thereby forming a coating film with a film thickness shown in Table 4. The surface resistivity of the formed coating film is shown in Table 4. In addition, the evaluation results of the viscosity stability of a part of the obtained carbon material dispersion, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 5.

[0192] Table 4

[0193]

[0194] Table 5

[0195]

[0196] <Preparation and evaluation of dispersion (2)>

[0197] (Mixed liquid 40~54)

[0198] The first dispersion, the second dispersion, and the third dispersion before adding the binder resin of the types shown in Table 6 were mixed so that the carbon material 1, the carbon material 2, and the carbon material 3 had the mass ratio shown in Table 6, and then mixed using a magnetic stirrer to obtain a mixed solution. The evaluation results of the viscosity stability of a part of the obtained mixed solution, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 7.

[0199] Table 6

[0200]

[0201] Table 7

[0202]

[0203] (Examples 38 to 50, Reference Examples 9 to 12, Comparative Examples 5 to 6)

[0204] The mixed liquids and binders of the types shown in Table 8 were blended at a ratio such that the concentration of the carbon material in the formed coating film (solid content) became the value (%) shown in Table 8, and then mixed using a magnetic stirrer to obtain a carbon material dispersion. The obtained carbon material dispersion was applied to a PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) with a thickness of 100 μm using a rod coater, and then dried in an electric oven at 90°C for 30 minutes to remove volatile components, thereby forming a coating film with a film thickness shown in Table 8. The surface resistivity of the formed coating film is shown in Table 8. In addition, the evaluation results of the viscosity stability of a portion of the obtained carbon material dispersion, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 9.

[0205] Table 8

[0206]

[0207] Table 9

[0208]

[0209] <Preparation and evaluation of dispersion (3)>

[0210] (Mixed liquid 55~58)

[0211] Place the dispersant and water of the type and amount shown in Table 10 in a polyethylene bottle (polyethylene bottle) with a capacity of 200 mL. After stirring with a magnetic stirrer until uniform, add the carbon material of the type and amount shown in Table 10 and stir. Next, use a high-pressure homogenizer (manufactured by Changguang Co., Ltd.) to carry out high-pressure treatment under the condition of a treatment pressure of about 10 MPa. Thereafter, use a high-pressure homogenizer (manufactured by Sugino Machine Limited) to carry out high-pressure dispersion treatment under the condition of a treatment pressure of about 100 MPa to obtain a mixed solution. The evaluation results of the viscosity stability of the obtained mixed solution, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 11.

[0212] Table 10

[0213]

[0214] Table 11

[0215]

[0216] (Examples 51 to 54)

[0217] The mixed solution and the binder of the types shown in Table 12 were mixed so that the concentration of the carbon material in the formed coating film (solid content) became the value (%) shown in Table 12, and then mixed using a magnetic stirrer to obtain a carbon material dispersion. The obtained carbon material dispersion was applied to a PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) with a thickness of 100 μm using a rod coater, and then dried in an electric oven at 90°C for 30 minutes to remove the volatile components, thereby forming a coating film with a film thickness shown in Table 12. The surface resistivity of the formed coating film is shown in Table 12. In addition, the evaluation results of the viscosity stability of the obtained carbon material dispersion, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 13.

[0218] Table 12

[0219]

[0220] Table 13

[0221]

[0222] <Manufacturing of Dispersant (2)>

[0223] (Dispersants α, β, and γ)

[0224] Dispersants α, β, and γ were produced according to the above-described production methods of dispersants a and b. The properties of the produced dispersants α, β, and γ are shown below.

[0225] Dispersant α: Random copolymer, AN:AA (mass ratio) = 70:30, Mn 61,100, PDI 2.24, solid content 24.3%

[0226] Dispersant β: Block copolymer

[0227] (i) A chain AN:AA (mass ratio) = 80:20, Mn 45,500

[0228] (ii) B chain AN:AA (mass ratio) = 48.5:51.5, Mn 16,500

[0229] (iii) Overall Mn 62,000, PDI 1.44, solid content 29.7%

[0230] Dispersant γ: Block copolymer

[0231] (i) A chain AN:AA (mass ratio) = 80:20, Mn 21,200

[0232] (ii) B chain AN:AA (mass ratio) = 48.5:51.5, Mn 40,500

[0233] (iii) Overall Mn 61,700, PDI 1.54, solid content 29.1%

[0234] <Preparation and evaluation of dispersion (4)>

[0235] (Dispersion liquids a-1 to 3, b-1 to 3)

[0236] The dispersant and water of the type and amount shown in Table 14 are placed in a polyethylene bottle (polyethylene bottle) with a capacity of 200 mL. After stirring with a magnetic stirrer until uniform, the carbon material of the type and amount shown in Table 14 is added and stirred. Next, a high-pressure homogenizer (manufactured by Changguang Co., Ltd.) is used to perform high-pressure treatment under the condition of a treatment pressure of about 10 MPa. Thereafter, a high-pressure homogenizer (manufactured by Sugino Machine Limited) is used to perform high-pressure dispersion treatment under the condition of a treatment pressure of about 100 MPa to obtain a dispersion before adding a binder resin.

[0237] Table 14

[0238]

[0239] (Mixed solution α, β, γ)

[0240] The first dispersion and the second dispersion before adding the binder resin of the types shown in Table 15 were mixed so that the carbon material 1 and the carbon material 2 had the mass ratio shown in Table 15, and then mixed using a magnetic stirrer to obtain a mixed solution. The evaluation results of the viscosity stability of the obtained mixed solution, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 16.

[0241] Table 15

[0242]

[0243] Table 16

[0244]

[0245] (Examples 55 to 57)

[0246] The mixed solution and the binder of the types shown in Table 17 were mixed so that the concentration of the carbon material in the formed coating film (solid content) became the value (%) shown in Table 17, and then mixed using a magnetic stirrer to obtain a carbon material dispersion. The obtained carbon material dispersion was applied to a PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) with a thickness of 100 μm using a rod coater, and then dried in an electric oven at 90°C for 30 minutes to remove the volatile components, thereby forming a coating film with a film thickness shown in Table 17. The surface resistivity of the formed coating film is shown in Table 17. In addition, the evaluation results of the viscosity stability of the obtained carbon material dispersion, the results of the observation of aggregates, and the absorbance ratio (A 380 / A 780 ) are shown in Table 18.

[0247] Table 17

[0248]

[0249] Table 18

[0250]

[0251] (Application Example 1: Manufacturing method for scale-up)

[0252] 239 parts of dispersant b and 9,721 parts of water were placed in a stainless steel container with a capacity of 20L. Stir with a dissolver until uniform, add 40 parts of SWCNT-1 little by little while stirring, and stir for 1 hour. Use a homogenizer (made by SMT Co., Ltd.) to mix thoroughly by treating it in a circulation form for 4 times. Next, use a high-pressure homogenizer (made by Changguang Co., Ltd.) with a nozzle with an inner diameter of 0.44mm, and treat it in a circulation form for a time equivalent to 10 times under a treatment pressure of 2 to 50MPa. Thereafter, use a high-pressure homogenizer (made by Sugino Machine Limited) with a nozzle with an inner diameter of 0.1mm, and treat it in a circulation form for a time equivalent to 5 times under a treatment pressure of 150MPa. Similarly, 398 parts of dispersant b and 100 parts of MWCNT-1, 717 parts of dispersant b and 600 parts of CB-1 were used to prepare dispersions before adding the binder resin, respectively, with the total amount of water changed in a manner to be 10,000 parts. The respective solutions were mixed while stirring with a dissolver in a manner such that the carbon material ratio became SWCNT-1:MWCNT-1:CB-1=1:30:3.34, to obtain a mixed dispersion before adding the binder resin. The evaluation results of the viscosity stability of the obtained mixed dispersion and the results of the observation of aggregates were both "◎". While stirring the obtained mixed dispersion with a dissolver, binder A was added in an amount such that the concentration of the carbon material in the total solid content was 3%. The evaluation results of the viscosity stability of the carbon material dispersion after the binder resin was added and the results of the observation of aggregates were both "◎". After that, the film was coated on a 100 μm thick PET film (trade name "Lumirror", manufactured by Toray Industries, Inc.) using a bar coater, and then dried in an electric oven at 90°C for 30 minutes to remove volatile components to form a coating film. The carbon material concentration in the coating film was 3%, the film thickness of the coating film was 1 μm, and the surface resistivity of the coating film was 5.2×10 4 Ω / sq.

[0253] In Application Example 1, a dispersion of each carbon material before adding a binder resin is prepared, and the prepared dispersions are mixed to obtain a carbon material dispersion containing a plurality of carbon materials at a specified ratio. It should be noted that all carbon materials can be added in the initial stage and dispersed. In addition, carbon materials and dispersants can also be added in the middle of the dispersion. For example, SWCNT and dispersant can be added to a dispersion containing MWCNT and dispersant and dispersed, and then CB and dispersant can be added and dispersed.

[0254] (Application Example 2-1: Battery Materials (Negative Electrode))

[0255] The following materials are used to manufacture the negative electrode of a lithium-ion battery.

[0256] [Negative electrode active agent]

[0257] Graphene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0258] ·Silicon monoxide (manufactured by Fujifilm and Wako Pure Chemical Industries, Ltd.)

[0259] [Binder]

[0260] 10% polyacrylic acid aqueous solution (trade name "CLPA-C07", manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)

[0261] Carboxymethyl cellulose (trade name "CMC Daicel 2200", manufactured by Daicel Miraizu Ltd.)

[0262] Styrene butadiene copolymer latex (trade name: "NALSTER SR-112", manufactured by NIPPON A&L INC.)

[0263] Using a planetary mixer, 15 parts of silicon monoxide, 85 parts of graphene, 3 parts of mixed solution 40, 30 parts of 10% polyacrylic acid aqueous solution, 1.6 parts of carboxymethyl cellulose, and 0.4 parts of styrene butadiene copolymer latex were mixed, and a smear was used to obtain a negative electrode material with a unit area mass of 15 mg / cm after drying. 2 The negative electrode material was coated on a copper foil with a thickness of 20 μm in a manner. It should be noted that other mixing devices such as a rotation / revolution mixer can be used for mixing. After being placed in an oven set at 120°C for 30 minutes to dry, it was rolled by roller pressing to obtain a negative electrode. The volume resistivity of the obtained negative electrode was 0.14Ω·cm, and the capacity retention rate was 95%.

[0264] (Application Example 2-2: Battery Materials (Anode))

[0265] The negative electrode was manufactured in the same manner as in the aforementioned application example 2-1 except that the mixed solution 38 was used instead of the mixed solution 40. The volume resistivity of the manufactured negative electrode was 0.39 Ω·cm and the capacity retention rate was 93%. Based on the above, it can be seen that by using a mixed solution with good dispersion evaluation, a negative electrode with a smaller volume resistivity value can be manufactured.

[0266] (Application Example 3-1: Antistatic Coating Agent)

[0267] 100g of mixed solution 40, 100g of polymer binder (trade name "NeoPac R-9699", manufactured by Kusumoto Chemicals Co., Ltd., acrylic urethane resin, solid content 40%), and 800g of pure water were placed in a plastic cup (polycup), and stirred with a dissolver to obtain an antistatic coating agent. Using a rod coater, the obtained antistatic coating agent was applied to the surface of a polyethylene terephthalate film (manufactured by Toray Industries, Inc.) with a thickness of 38μm in such a way that the coating film after drying became 0.5μm. It was placed in an oven set at 80°C for 10 minutes to dry it to obtain an antistatic coating film. The surface resistivity of the obtained film was 9.8×10 5 Ω / cm 2 .

[0268] (Application Example 3-2: Antistatic Coating Agent)

[0269] The antistatic coating film was produced in the same manner as in Application Example 3-1 except that the mixed solution 38 was used instead of the mixed solution 40. The surface resistivity of the produced film was 5.7×10 7 Ω / cm 2 Based on the above, it can be seen that by using a mixed liquid with a good dispersion evaluation, an antistatic coating film with a smaller surface resistivity value can be produced.

[0270] Industrial Applicability

[0271] The carbon material dispersion of the present invention is useful as a constituent material of coatings, inks, resin molded products, etc. exhibiting properties such as high electrical conductivity and high thermal conductivity, and is suitable for various applications such as battery materials, electronic component trays, IC chip covers, electromagnetic wave shielding, automotive components, and robot components.

Claims

1. A carbon material dispersion liquid comprising: at least two carbon materials selected from the group consisting of single-walled carbon nanotubes, multi-walled carbon nanotubes and carbon black; an aqueous medium; a dispersant; and a binder resin, The carbon material dispersion liquid satisfies the following necessary conditions (1) and (2), The surface resistivity a (Ω / sq) and the surface resistivity b (Ω / sq) satisfy the relationship a < b, where, The surface resistivity a (Ω / sq) is the surface resistivity of a first coating having a carbon material content of 3% by mass and a thickness of 1 μm, which is formed by applying and drying the carbon material dispersion. The surface resistivity b (Ω / sq) is the surface resistivity of a second coating having a carbon material content of 3% by mass and a thickness of 1 μm formed by applying and drying a reference dispersion, wherein the reference dispersion has the same composition as the carbon material dispersion except that it does not contain one of the carbon materials. The surface resistivity a is 5.0×10 5 Ω / sq or less, (1) When the carbon material is a combination of the single-walled carbon nanotube and the carbon black, the amount of the carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the single-walled carbon nanotube, When the carbon material is a combination of the multi-walled carbon nanotubes and the carbon black, the amount of the carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the multi-walled carbon nanotubes. When the carbon material is a combination of the single-walled carbon nanotube and the multi-walled carbon nanotube, the amount of the multi-walled carbon nanotube is 10 to 100 parts by mass relative to 1 part by mass of the single-walled carbon nanotube. When the carbon material is a combination of the single-walled carbon nanotubes, the multi-walled carbon nanotubes, and the carbon black, the amount of the carbon black is 0.001 to 0.43 parts by mass relative to 1 part by mass of the total of the single-walled carbon nanotubes and the multi-walled carbon nanotubes, and the amount of the multi-walled carbon nanotubes is 10 to 100 parts by mass relative to 1 part by mass of the single-walled carbon nanotubes, (2) The surface resistivity of a dry film having a carbon material content of 3% by mass and a thickness of 1 μm is 1.0×10 6 Ω / sq or less.

2. The carbon material dispersion according to claim 1, wherein The dispersant is at least any one of a polymer dispersant and a cellulose derivative, The polymer dispersant is a polymer having a structural unit (1) derived from (meth)acrylonitrile and a structural unit (2) derived from (meth)acrylic acid.

3. The carbon material dispersion according to claim 2, wherein The polymer dispersant is a polymer having a carboxyl group at least partly neutralized with a base, and comprising 50 to 80% by mass of the structural unit (1) and 20 to 50% by mass of the structural unit (2), wherein the total of the structural unit (1) and the structural unit (2) is 100% by mass.

4. The carbon material dispersion according to claim 3, wherein The polymer is an AB block copolymer comprising a polymer segment A and a polymer segment B, The polymer segment A comprises 60 to 95% by mass of a structural unit (1-A) derived from acrylonitrile and 5 to 40% by mass of a structural unit (2-A) derived from methacrylic acid, wherein the total of the structural unit (1-A) and the structural unit (2-A) is 100% by mass. The polymer segment B comprises 10 to 70% by mass of a structural unit (1-B) derived from acrylonitrile and 30 to 90% by mass of a structural unit (2-B) derived from methacrylic acid, wherein the total of the structural unit (1-B) and the structural unit (2-B) is 100% by mass. The number average molecular weight of the polymer segment A is 10,000 to 100,000, and the molecular weight distribution is less than 1.

8. The number average molecular weight of the polymer segment B is 3,000 to 200,000.

5. The carbon material dispersion according to claim 1, wherein The binder resin is at least one selected from the group consisting of cellulose derivatives, styrene-butadiene copolymers, and acrylic resins.

6. The carbon material dispersion according to any one of claims 1 to 5, wherein When the carbon material includes the single-walled carbon nanotubes, the amount of the dispersant is 30 to 200 parts by mass relative to 100 parts by mass of the single-walled carbon nanotubes. When the carbon material includes the multi-walled carbon nanotubes, the amount of the dispersant is 30 to 200 parts by mass relative to 100 parts by mass of the multi-walled carbon nanotubes. When the carbon material includes the carbon black, the amount of the dispersant is 10 to 200 parts by mass based on 100 parts by mass of the carbon black.

7. The carbon material dispersion according to any one of claims 1 to 5, wherein The average length of the single-walled carbon nanotubes is 5 to 600 μm. The average length of the multi-walled carbon nanotubes is 40 to 3,000 μm.

8. The carbon material dispersion according to any one of claims 1 to 5, which is obtained by mixing a first dispersion and a second dispersion. The first dispersion contains at least one of the carbon materials. The second dispersion contains at least one of the carbon materials that is different from the carbon material in the first dispersion.

9. The carbon material dispersion according to any one of claims 1 to 5, wherein The absorbance at a wavelength of 380 nm of the dilute dispersion obtained by diluting with a blank solution so that the absorbance at a wavelength of 580 nm becomes 1.8 ± 0.02 is A L Absorbance A relative to wavelength 780nm H The ratio (A L / A H ) is 1.40 or more, and the blank solution has the same composition as the carbon material dispersion solution except that it does not contain the carbon material.

10. Use of the carbon material dispersion according to any one of claims 1 to 5 for producing any product selected from the group consisting of paint, ink, coating agent, resin molded product material, conductive material, thermal conductive material, and antistatic material.

11. Use of the carbon material dispersion according to any one of claims 1 to 5 for producing a product including a battery material and a mechanical part having a coating film formed of the carbon material dispersion.

Citation Information

Patent Citations

  • Catalyst for carbon nanotube synthesis

    JP2015123410A

  • Conductive material dispersion and use thereof

    JP2021190331A

  • Carbon nanotube dispersion and use thereof

    JP2022079409A

  • Carbon nanotube aqueous dispersion, conductive film, electrode, and solar cell and method for producing same

    WO2022064939A1